The fire, the water, and Maudie McGinn - Pla, Sally J. (Quill Tree Books, an imprint of HarperCollins Publishers, 2023)
Follows thirteen-year-old neurodivergent Maudie during an eventful summer in California with her father, where she struggles with whether to share a terrible secret about life with her mom and stepdad